Immunohistochemical expression of p53, BCL-2, BAX and VEGFR1 proteins in nephroblastomas A expressão imuno-histoquímica das proteínas p53, BCL-2, BAX e VEGFR1 em nefroblastomas - Ana Paula Percicote; Fernanda El Ghoz Leme; Tammy Vernalha Rocha Almeida; Ana Karyn Ehrenfried Freitas; Elizabeth Schneider Gugelmin; Lúcia de Noronha (Sociedade Brasileira de Patologia Clínica, 2013)
INTRODUCTION: Nephroblastoma or Wilms' tumor is the most frequent renal cancer in children. Although its prognosis is favorable for most patients, it may relapse or have a fatal outcome. The characterization of risk groups by applying immunohistochemical biomarkers aims to adapt the treatment to its corresponding group as well as to reduce relapses and fatal outcome. p53, B-cell lymphoma 2 (BCL-2), BCL-2 associated protein X (BAX) and vascular endothelial growth factor receptor 1 (VEGFR1) are among the most widely studied biomarkers, which are related to the apoptotic pathway, DNA repair and neovascularization. OBJECTIVE: The objective of this study is to assess the immunohistochemical expression of p53, BCL-2, BAX and VEGFR1 in samples of human nephroblastoma and to correlate them with clinicopathological prognostic factors. MATERIAL AND METHODS: Twenty-nine surgical specimens of nephroblastoma diagnosed from 1994 to 2007 were selected from the Anatomopathological Service of two hospitals in Curitiba. The immunohistochemical analysis of tissue microarrays was performed through immunoperoxidase staining and the yielded results were compared with clinicopathological prognostic factors. RESULTS: The major immunohistochemical expression of VEGFR1 in blastema and epithelium presented positive association with the risk group. Hence this may be related to higher vascular neoplastic invasion apparently caused by the endothelial growth factor, which maximizes the chances of metastasis and ultimately changes tumor staging, risk group and clinical evolution. CONCLUSIONS: The immunohistochemical expression of VEGFR1 substantiated a directly proportional association with the nephroblastoma risk group. INTRODUÇÃO: O nefroblastoma, ou tumor de Wilms, é a neoplasia renal mais frequente na infância. Embora o prognóstico seja favorável para a maioria dos pacientes, muitos evoluem para recidiva ou óbito. A caracterização de grupos de risco por meio de marcadores imuno-histoquímicos tem por objetivo adequar o tratamento ao grupo de risco e reduzir recidivas e óbitos. Entre os marcadores mais estudados estão p53, B-cell lymphoma 2 (BCL-2), BCL-2 associated protein X (BAX) e fator de crescimento vascular endotelial e seu receptor 1 (VEGFR1), relacionados com a via apoptótica, o reparo do ácido desoxirribonucleico (DNA) e a neovascularização. OBJETIVO: O objetivo deste estudo é avaliar a expressão imuno-histoquímica de p53, BCL-2, BAX e VEGFR1 em amostras de nefroblastoma humano e correlacioná-las com fatores prognósticos clínico-patológicos. MATERIAL E MÉTODO: Foram utilizadas 29 amostras de nefroblastomas retiradas dos Serviços de Anatomia Patológica de dois hospitais de Curitiba, com diagnósticos entre 1994 e 2007. Por meio da técnica de imunoperoxidase, com as amostras em arranjo tecidual em matriz, realizou-se análise da imuno-histoquímica desses marcadores e sua comparação com fatores prognósticos clínico-patológicos. RESULTADOS: A maior imunoexpressão de VEGFR1 nos componentes blastematoso e epitelial mostrou associação positiva ao grupo de risco, sendo que isso poderia estar relacionado com a maior capacidade de invasão vascular neoplásica que pode ser conferida por esse fator de crescimento endotelial, aumentando, assim, as chances de metástases e alterando o estadimento, o grupo de risco e a evolução clínica. CONCLUSÃO: A expressão imuno-histoquímica aumentada de VEGFR1 mostrou associação diretamente proporcional ao grupo de risco dos pacientes com nefroblastoma.